Effectiveness Analysis of Gamification Based on Google TV - Setiawan, Fajar (Department of Informatics Universitas Islam Indonesia, 2025)
This study analyzes the effectiveness of gamification implemented on the Google TV platform to enhance user engagement and satisfaction. The research employs a mixed-method approach, combining quantitative data from user interactions and qualitative feedback from surveys. Results indicate a significant improvement in user retention and interaction rates when gamification elements such as badges, leaderboards, and challenges are integrated. The rapid growth of smart TV adoption in Indonesia (reaching 35% household penetration in 2023) has intensified competition among streaming platforms, creating a need for innovative engagement strategies. This study examines the effectiveness of gamification implementation on Google TV in increasing user retention and satisfaction. The research was motivated by the lack of localized studies on gamification in Indonesia's unique digital ecosystem, where cultural factors significantly influence user behavior. Using a sequential mixed-method approach, we first conducted quantitative analysis of 400 users' interaction data over three months, followed by in-depth interviews with 30 selected participants. The results demonstrate a 27% increase in average viewing duration (p=0.008) and 22% improvement in NPS scores after gamification implementation. However, qualitative findings reveal technical barriers including interface complexity for elderly users and latency issues during peak hours.